The production process of chepa shutki: A traditional Bangladeshi fermented fish product - Jasmin Ara Farhana; Sijmen E. Schoustra; Ferdous Ahamed; Bas Zwaan; Oscar van Mastrigt (Heliyon)
Chepa shutki is a sticky, solid, fermented, salt-free product from Bangladesh prepared from small-sized fish by local producers. It can be consumed as a chutney or sauce-like recipe or shutki curry with vegetables as a side dish for rice or bread. Chepa shutki is manufactured according to a small-scale traditional technique relying on spontaneous fermentation. Although chepa shutki is an important part of the human diet in Bangladesh, providing flavour as well as essential nutrients (especially protein and bone minerals), research on variations in production of chepa shutki has been limited. The aim of this study was to determine the variations in processing methods of chepa shutki and identify production process parameters. A survey was carried out with respondents using structured questionnaires and observations on current processing practices and the equipment used. In Bangladesh, chepa shutki is produced from different small fish (Puntius, Setipinna and Otolithoides) referred to as punti, phaisha and puma type, respectively. Among these, the punti type is produced the most and puma type the least. After washing, sun drying, soaking and overnight storage, fermentation takes place in airtight earthen pots (locally called motka) whose micropores are blocked with fish oil to ensure anaerobic conditions. The fermentation duration varies from three to twelve months. Types of fish, types of fermentation container (old/new) and fermentation time were identified as vital process parameters. This information is crucial for further studies to understand how processing variations affect product properties and to develop a standard processing method to produce consistently high quality chepa shutki with good preservation properties.